Perceived Stigma and Self-Efficacy of Patients With Inflammatory Bowel Disease-Related Stoma in China: A Cross-Sectional Study - Wang, Yuting; Li, Shuyan; Gong, Jianfeng; Cao, Lei; Xu, Dingting; Yu, Qiao; Wang, Xiaoying; Chen, Yan (Frontiers in Medicine, 2022)
Background Patients with inflammatory bowel disease (IBD)-related stoma face physical, psychological, and social adjustment challenges. However, knowledge about stigmatization and self-management, which is important for clinical care and patient education strategies, is lacking. Objective To evaluate the level of stigma and self-management ability of Chinese patients with IBD-related stoma using an online questionnaire. Methods Participants were recruited from two general hospitals in mainland China and the internet platforms of the China Crohn's and Colitis Foundation (CCCF). Participants completed a questionnaire, which gathered data on sociodemographic, clinical, and experience in online groups, self-efficacy scale, and social impact scale. The influencing factors of self-efficacy and perceived stigma were assessed by stepwise multivariate regression analyses. Results One hundred and seventy-six respondents were included. Most of the respondents (78/176, 44.32%) spent between 500 and 999 RMB (77–153) on ostomy care accessories monthly. Three patients reported using homemade ostomy products. The average score on the self-efficacy scale was 75.79 ± 23.91, which reflected a moderate level of self-efficacy, and 69 (39.2%) respondents had low-level self-efficacy. The average social impact scale score was 62.76 ± 12.69, which reflected a moderate level of perceived stigma. Forty-three (24.43%) patients experienced severe levels of perceived stigma. Stepwise multivariate regression analysis revealed that self-efficacy was associated with educational level (P = 0.007), whereas stigma was associated with nursing privacy (P = 0.021) and acceptance by the closest person (P = 0.005). A total of 91% of respondents who participated in online peer support groups believed the groups were helpful for disease management. Conclusions Chinese patients with IBD-related stoma reported a moderate degree of perceived stigma; their level of self-efficacy was low to moderate. High educational level was associated with high self-efficacy. Notably, acceptance of the stoma by the closest person was an influencing factor protecting patients from perceived stigma. Interventions aimed at improving patient education, reducing economic burden, and strengthening social support should be considered to help improve the living conditions of patients with IBD-related stoma.